The case of Peter: reflections on applied ethics in a neonatal intensive care unit. Issue 1 (2nd January 2016) - Willsher, Kerre A.
Abstract: The case of Peter is reflected upon in order to highlight some of the moral theorising that could be brought to bear in the process of providing palliative care for sick neonates. The situation will be discussed using the theoretical lenses of deontological and virtue ethics. Nursing practice is considered as engaged moral reasoning where the nurse brings his/her beliefs, knowledge and experience into the situation and engages in reflexivity to provide appropriate ongoing patient care. The care should be provided in culturally sensitive manner and tailored to the needs of the newborn and their family. Nurses should initiate early consultations with colleagues, medical staff and families to address concerns about patient well-being in order to enhance the well-being of patients and families and to improve the work environment making it more conducive to care.